2022
DOI: 10.1039/d2py00898j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and visualization of bottlebrush-shaped segmented hyperbranched polymers

Abstract: Visualization of single molecular morphology provides an intuitive evidence to understand the relationships of molecular structure-synthetic method. Herein, by combining the architectural features of molecular bottlebrush (MBB) and segmented hyperbranched...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Up to now, a variety of approaches have been developed for the synthesis of MBBs, which can be summarized into three strategies, including grafting-from, grafting-onto, and grafting-through. Among these approaches, the grafting-through strategy combined with ring-opening metathesis polymerization (ROMP) of macromonomers (MMs) is promising, since precise MBBs with a perfectly accurate grafting density of 100% and block sequence can be easily synthesized. However, for preparing water-soluble MBBs with functional groups, such as tertiary amine and hydroxy groups, there are particularly clear challenges due to the inevitable catalyst decomposition induced by MMs with electron-donating groups as well as polar or protic solvents, leading to ROMP with low initiation efficiency and slow polymerization kinetics. Recently, O’Reilly , and Pokorski et al reported that the presence of chloride ions could significantly suppress the decomposition of the Grubbs catalyst and lead to better control of polymerization, which provides a great opportunity to synthesize water-soluble polynorbornenes (PNB) via aqueous ROMP. However, considering the above-mentioned challenges of synthesis of water-soluble MBBs, as far as we know, reports so far have been rarely reported to directly synthesize water-soluble MBBs by using aqueous ROMP via the grafting-through strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, a variety of approaches have been developed for the synthesis of MBBs, which can be summarized into three strategies, including grafting-from, grafting-onto, and grafting-through. Among these approaches, the grafting-through strategy combined with ring-opening metathesis polymerization (ROMP) of macromonomers (MMs) is promising, since precise MBBs with a perfectly accurate grafting density of 100% and block sequence can be easily synthesized. However, for preparing water-soluble MBBs with functional groups, such as tertiary amine and hydroxy groups, there are particularly clear challenges due to the inevitable catalyst decomposition induced by MMs with electron-donating groups as well as polar or protic solvents, leading to ROMP with low initiation efficiency and slow polymerization kinetics. Recently, O’Reilly , and Pokorski et al reported that the presence of chloride ions could significantly suppress the decomposition of the Grubbs catalyst and lead to better control of polymerization, which provides a great opportunity to synthesize water-soluble polynorbornenes (PNB) via aqueous ROMP. However, considering the above-mentioned challenges of synthesis of water-soluble MBBs, as far as we know, reports so far have been rarely reported to directly synthesize water-soluble MBBs by using aqueous ROMP via the grafting-through strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Chen et al reported the synthesis of branched MBBs via a combination of self-condensing vinyl polymerization (SCVP) and an accelerated CuAAC grafting-onto strategy. [36] The accelerated CuAAC reaction allows the branched MBBs have high G dst (up to 2.7 side chains per backbone unit). The unimolecular morphology of these branched MBBs were visualized by atomic force microscopy (AFM) directly.…”
Section: The Mbbs With Branched Backbonementioning
confidence: 99%
“…A) Chemical structures of ionomers 1, 2, 3, and 4, B) the synthesis route of branched MBBs via a combination of SCVP and an accelerated CuAAC reaction and C) AFM height images of the resultant branched MBBs. Reproduced with permission [36]. Copyright 2022, Royal Society of Chemistry.…”
mentioning
confidence: 99%
“…With the development of synthetic chemistry, a variety of efficient and controllable synthetic techniques, such as atom transfer radical polymerization (ATRP), reversible addition–fragmentation chain transfer (RAFT) polymerization, and ring-opening metathesis polymerization (ROMP) have been discovered, making it possible to obtain MBBs with tunable sizes, morphologies, and functions for many practical applications. There have been a few existing reviews on MBBs, which primarily concentrate on aspects such as synthesis, self-assembly behavior, or general discussions on applications. However, they do not delve into great detail regarding the potential use of MBBs as nanocarriers for biomedical purposes. Recognizing this gap in the literature, we explore and discuss this specific aspect in our Review.…”
Section: Introductionmentioning
confidence: 99%